2020
DOI: 10.1177/0145561320943362
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for the Recurrence of Benign Paroxysmal Positional Vertigo: A Systematic Review and Meta-Analysis

Abstract: Objective: Benign paroxysmal positional vertigo (BPPV) has a high recurrence rate, but the risk factor–associated recurrence are elusive. Methods: Searches were performed in PubMed, Embase, Cochrane library, Web of science, Chinese National Knowledge Infrastructure, and Sino Med up to November 3, 2019. The effect size was analyzed by odds ratio and 95% CI. Data from eligible studies were meta-analyzed using Stata version 15.0. Results: Our search resulted in a total of 4076 hits. Twenty-four outcomes of sixty … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 112 publications
3
31
0
Order By: Relevance
“…We demonstrated the higher recurrence rate of BPPV among female patients and those with low BMD (osteopenia/osteoporosis), which were consistent with the previous results [10][11][12]23].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…We demonstrated the higher recurrence rate of BPPV among female patients and those with low BMD (osteopenia/osteoporosis), which were consistent with the previous results [10][11][12]23].…”
Section: Discussionsupporting
confidence: 92%
“…However, including our study, the other studies showed a similar recurrence rate of posttraumatic BPPV compared with idiopathic one [22]. Moreover, type of the involved semicircular canals did not affect the recurrence rate of BPPV in our study, as replicated by other studies [10].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Prevention: BPPV is known to recur frequently. Reported rates of recurrence in BPPV vary considerably, ranging from 16 to 50% [52,53], and some reports correlated an increased rate of recurrence with aging [54,55]. In patients with recurrent BPPV, vitamin D deficiency was shown to be a relevant cofactor [56].…”
Section: Benign Paroxysmal Positional Vertigo (Bppv)mentioning
confidence: 99%